Validation of a score based on simple hematological parameters as a predictor of mortality in hospitalized patients due to COVID-19 - Azañero-Haro, Johan (2025)
Introduction: During the COVID-19 pandemic, clinical prediction rules such as the PAWNN score have been developed to estimate mortality risk using only a complete blood count. However, it has not yet been validated in the Peruvian and Latin American population. Material and methods: A validation study was conducted in a retrospective cohort of patients hospitalized with COVID-19 between March and December 2020. Sensitivity, specificity, predictive values, likelihood ratios, and the area under the receiver operating characteristic curve (AUROC) for the PAWNN score were calculated. Results: A total of 1,963 patients were included, with a median age of 58 years; 66.4% were male. The mortality rate was 46.9%. Using a cutoff of 6, sensitivity was 96%, specificity was 16%, and AUROC was 0.71 (95% CI: 0.69–0.73). Conclusion: The PAWNN score does not have adequate diagnostic performance to predict mortality in patients hospitalized due to COVID-19.